2016
DOI: 10.1038/scsandc.2015.34
|View full text |Cite|
|
Sign up to set email alerts
|

Esophageal perforation associated with fracture of the upper thoracic spine from blunt trauma: a case report

Abstract: We report the successful conservative management of an unusual case of esophageal perforation associated with an upper thoracic spinal fracture from blunt trauma in Minamata, Kumamoto, Japan. A 69-year-old man became paraplegic secondary to an L1 burst fracture caused by a boating accident and underwent posterior fixation on the day of admission. The patient also had a minimally displaced T4 vertebral fracture. Fever, dyspnea and elevated inflammatory markers all persisted postoperatively. Computed tomography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In our literature review, only nine previously reported cases of esophageal perforation associated with thoracic vertebral fractures have been published. Thus, esophageal perforation seems to be a very infrequent complication of thoracic vertebral fractures (Table 1) [2][3][4][5][6][7][8][9][10] . All reported cases were found to be caused by high-energy trauma, and all esophageal perforations occurred due to upper thoracic vertebral fractures between T1 and T4.…”
Section: Fracture: a Case Report And Literature Reviewmentioning
confidence: 99%
“…In our literature review, only nine previously reported cases of esophageal perforation associated with thoracic vertebral fractures have been published. Thus, esophageal perforation seems to be a very infrequent complication of thoracic vertebral fractures (Table 1) [2][3][4][5][6][7][8][9][10] . All reported cases were found to be caused by high-energy trauma, and all esophageal perforations occurred due to upper thoracic vertebral fractures between T1 and T4.…”
Section: Fracture: a Case Report And Literature Reviewmentioning
confidence: 99%
“…The proximity of the esophagus to the spinal column between C5 and T4 results in its vulnerability to spinal fracture, particularly hyperextension-type injuries, and possible esophageal disruptions and fistula formations. 4 …”
mentioning
confidence: 99%
“…The proximity of the esophagus to the spinal column between C5 and T4 results in its vulnerability to spinal fracture, particularly hyperextension-type injuries, and possible esophageal disruptions and fistula formations. 4 The treatment of an esophageal fistula can involve conservative management with enteral diversion or direct closure of the defect with direct repair and or in combination with vascularized tissue. [5][6][7] An esophageal fistula complication has been documented in the cervical spine, with incidence rates ranging from 0% to 3.4%, 8,9 although this complication in the high thoracic spine has not been as well documented.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Blunt ET is rare relative to penetrating ET and is postulated to cause ET because of high speed deceleration causing direct compression between the spine and surrounding structures. 11,12 In addition, the diagnosis of blunt ET is often delayed because of low clinical suspicion and other significant contributing injuries such as traumatic brain injury. 12 Therefore, we hypothesized that blunt trauma is associated with higher risk of death than penetrating trauma.…”
mentioning
confidence: 99%